The quality of Indonesian teachers in the digital era: A meta-analysis - Prihono, Eko Wahyunanto; Retnawati, Heri; Lapele, Fitria; Waluyo, Wisnu Budi (Jurnal Penelitian dan Evaluasi Pendidikan, 2022)
The objective of the study is to determine the influence of determinant factors on teacher quality in Indonesia in the digital era in kindergarten, elementary, junior high, and high school units. It was a quantitative research with a correlation meta-analysis approach. The data was secondary data collected from various research results in Indonesia on the scholar.google.com page. The results of the study were published from 2012 to 2022. Data analysis used JASP software to estimate aggregates, draw plot Forrest, and publication bias. The aggregates were estimated through correlation scores with fixed effect models. The results showed that the funnel plot 104 study had a sample size that varied with the asymmetric distribution. Therefore, the results of the study were free from potential publication bias. It was reinforced by the forest plot display using the Trim and Fill method as well as the summary effect display results. Thus, the level of information validity based on the fixed-effect model of factors that affect the quality of teachers in the digital era in Indonesia was valid.